PENGEMBANGAN MODEL PENERIMAAN SOCIAL MEDIA MARKETING DI KALANGAN MAHASISWA - Agung Cahyo Legowo; Bustanul Arifin Noer (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2017)
The internet has changed the life style of people and also the way people to communicate. After the existence of the internet, people can buy products from his home or office. Prior to the internet, people get information about a product through written advertising, but now the information can be quickly obtained or disseminated by the presence of second-generation internet, or Web 2.0 Customers can exchange information and influence each otherin product selection. This could happen through social media. Because the huge number of the social media users make companies use this medium, not only to inform but also to sell. Not all entrepreneurs succeed in this online business, but many also fail. This study proposes model developed by the Technology Acceptance Model (TAM) and Theory of Reasoned Action (TRA) to determine the factors that could affect the purchase intention online through Social Media Marketing. The data obtained from this study is 748, which is obtained through a question naire distributed at public universities and private individual in three cities in Indonesia (Surabaya, Malang and Banjarmasin). Confirmatory factor analysis was conducted to test the construct validity and reliability for each variable. By using Structural Equation Modeling (SEM) showed that the most influential factor on purchase intention is perceived use fulness, while subjective normin fluenced the purchase intention but had no effect on perceived usefulness. Keywords:  social media marketing, structural equation modeling, technology acceptance models, theory of reasoned action